2019
DOI: 10.1021/acs.jpclett.9b02567
|View full text |Cite
|
Sign up to set email alerts
|

Fast Peroxy Radical Isomerization and OH Recycling in the Reaction of OH Radicals with Dimethyl Sulfide

Abstract: Dimethyl sulfide (DMS), produced by marine organisms, represents the most abundant, biogenic sulfur emission into the Earth´s atmosphere. The gas-phase degradation of DMS is mainly initiated by the reaction with the OH radical forming first CH SCH O radicals from the dominant H-abstraction channel. It is experimentally shown that these peroxy radicals undergo a two-step isomerization process finally forming a product consistent with the formula HOOCH 2 SCHO. The isomerization process is accompanied by OH recyc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

19
137
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 86 publications
(158 citation statements)
references
References 46 publications
19
137
2
Order By: Relevance
“…The relationships observed between HPMTF, DMS, SO 2 , and SO 4 2− strongly suggest that HPMTF is formed by DMS oxidation, a conclusion that is supported by recent theoretical and laboratory oxidation studies that identify HOOCH 2 SCHO as a product of DMS autoxidation (16,17). Production of HPMTF in the atmosphere is initiated by the H abstraction reaction of OH with DMS and subsequent molecular oxygen (O 2 ) addition to produce the methylthioxymethyl-peroxy radical (CH 3 SCH 2 OO•).…”
Section: supporting
confidence: 52%
See 2 more Smart Citations
“…The relationships observed between HPMTF, DMS, SO 2 , and SO 4 2− strongly suggest that HPMTF is formed by DMS oxidation, a conclusion that is supported by recent theoretical and laboratory oxidation studies that identify HOOCH 2 SCHO as a product of DMS autoxidation (16,17). Production of HPMTF in the atmosphere is initiated by the H abstraction reaction of OH with DMS and subsequent molecular oxygen (O 2 ) addition to produce the methylthioxymethyl-peroxy radical (CH 3 SCH 2 OO•).…”
Section: supporting
confidence: 52%
“…Our model results show that once formed, the fate of CH 3 SCH 2 OO• depends on the competition between isomerization to •CH 2 SCH 2 OOH and reaction with hydroperoxyl radical (HO 2 ) and nitric oxide (NO). The estimated first-order rate of 2.1 s −1 at 293 K for the first H shift in CH 3 SCH 2 OO• (16) and the rate recently determined from laboratory kinetic studies, 0.23 s −1 at 295 K (17), are considerably greater than experimental and calculated autoxidation rates for analogous peroxy radicals (24,27,28). Using the multiconformer transition state theory (MC-TST) approach of Møller et al (27) (see SI Appendix, section 5, for details), which has shown good agreement with experimentally determined H shift rate coefficients (29), we calculate the first (and rate-limiting) H shift rate to be significantly slower (0.041 s −1 at 293 K) than previously determined (16).…”
Section: Ch 3 Sch 2 Oo• Can Undergo a Rapid Unimolecular H Shift To Formmentioning
confidence: 82%
See 1 more Smart Citation
“…DMS a has an atmospheric residence time of ~1 day (Khan et al, 2016) before removal mechanisms such as oxidation to SO 2 occur (Andreae & Crutzen, 1997; Barnes et al, 2006). However, Berndt et al (2019) suggest that DMS oxidation can occur far more rapidly via an isomerization pathway, as does Swan et al (2016) who suggests that DMS oxidation can occur in a matter of hours over warm, well‐lit tropical coral reef waters (Swan et al, 2016), where hydroxyl concentrations are high (Andreae & Crutzen, 1997). If DMS‐derived sulfates significantly influence AOD over the southern GBR, a positive correlation is expected between daily mean DMS a and AOD during calm conditions (≤ 2 m s −1 ).…”
Section: Methodsmentioning
confidence: 99%
“…According to the current knowledge, in the gas phase, the oxidation of DMS or its oxidation products through H-abstraction leads to a corresponding peroxyl radical, which can be further oxidised into an alkoxy radical. Recently, it was suggested that the methylthiomethylperoxyl radical (CH3SCH2O2) undergoes a rapid unimolecular H-shift (Wu et al, 2015;Berndt et al, 2019). The final stable product will be an oxidised organic sulfur compound that is characterised by an aldehyde and an organic hydrogen peroxide functionality.…”
Section: Lumping Of Simple Reactionsmentioning
confidence: 99%